2019
DOI: 10.3892/ol.2019.10422
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value and clinical significance of ultrasound combined with CT in cystic renal cell carcinoma

Abstract: This study investigated the value and clinical significance of ultrasound combined with CT in the diagnosis of cystic renal cell carcinoma. A total of 85 patients with cystic renal cell carcinoma, who were admitted to the Oncology Department of Yantai Yuhuangding Hospital Affiliated to Qingdao University from December 2015 to April 2017, were selected as the study group, and 70 patients with benign renal cyst, who were examined in Yantai Yuhuangding Hospital Affiliated to Qingdao University, were selected as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…Some studies showed that CT was significantly better than US in screening of wall or septa nodule. 29,30 From our obtained results, there were 13 Bosniak grade IV by CEUS (EFSUMB 2020) and CEUS (V2019) compared to 15 cases of Bosniak grade IV by CECT (V2019). From Figure 11, we can see a nodule on the septation by CEUS, while it cannot be discovered by CECT.…”
Section: Discussionmentioning
confidence: 86%
“…Some studies showed that CT was significantly better than US in screening of wall or septa nodule. 29,30 From our obtained results, there were 13 Bosniak grade IV by CEUS (EFSUMB 2020) and CEUS (V2019) compared to 15 cases of Bosniak grade IV by CECT (V2019). From Figure 11, we can see a nodule on the septation by CEUS, while it cannot be discovered by CECT.…”
Section: Discussionmentioning
confidence: 86%
“…Although CRCC and CCDC have been relatively well described in pathology studies, comparative study of CT appearances are scanty, particularly in combination with histopathologic examination. However, patients with CRCC have a better prognosis after undergoing total nephrectomy or local resection than that CCDC [ 9 , 10 ]. So, an accurate diagnosis is important for guiding clinical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Computed tomography (CT) imaging is highly preferred by radiologists in diagnosing kidney abnormality due to its capability to produce highresolution images characterized by clear anatomical details, optimal contrast, and superior spatial resolution [4]. However, radiologists and nephrologists may occasionally encounter challenges in accurately diagnosing certain cases, leading to the possibility of misdiagnosis [9]. Furthermore, the current standard CT screening procedures are frequently associated with exorbitant financial costs [10].…”
Section: Introductionmentioning
confidence: 99%